1986
DOI: 10.1111/j.1348-0421.1986.tb03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Salmonella typhi Strains in HeLa S3 Monolayer Cells

Abstract: The internalization and intracellular multiplication, i.e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…K. pneumoniae Ca0438 replicated within intestinal epithelial cells during the first 6 h after the addition of gentamicin and survived for ϳ72 h. One study of S. Typhimurium showed an increased number of intracellular bacteria within 24 h inside MDCK epithelial cells (54). Another study also reported that a Salmonella enterica serovar Typhi clinical isolate increased within 24 h inside HeLa cells (55). A K. pneumoniae UTI isolate in a previous study was reported to replicate inside bladder epithelial cells within 4 h and survived for at least 96 h (24).…”
Section: Discussionmentioning
confidence: 86%
“…K. pneumoniae Ca0438 replicated within intestinal epithelial cells during the first 6 h after the addition of gentamicin and survived for ϳ72 h. One study of S. Typhimurium showed an increased number of intracellular bacteria within 24 h inside MDCK epithelial cells (54). Another study also reported that a Salmonella enterica serovar Typhi clinical isolate increased within 24 h inside HeLa cells (55). A K. pneumoniae UTI isolate in a previous study was reported to replicate inside bladder epithelial cells within 4 h and survived for at least 96 h (24).…”
Section: Discussionmentioning
confidence: 86%
“…Viable bacteria of strain 10007 were found to internalize into monolayered HeLa cells within 10 min after inoculation, and multiplied intracellularly (10). Ultrastructural findings of this phenomenon were also described and illustrated in a following paper (11).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial strains used in this study were S. enterica serovar Typhi GIFU10007 [17], z66 antigen-positive strains of S. enterica serovar Typhi isolated in India (S2) and Indonesia (S4-S8), S. enterica serovar Typhi Ty2, and z66 antigen-negative strains of S. enterica serovar Typhi isolated in Japan (S1 and S3) and Thailand (T1 and T2). E. coli DH5a was used for cloning with the pGEM Ò -T Easy vector (Promega).…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%